Pengaruh Manajemen Modal Kerja Terhadap Kinerja Perusahaan: Studi Kasus pada Perusahaan Ritel yang Terdaftar di BEI Periode 2018-2022 - Ghina Yasmin Mumtaz (Sanskara Manajemen Dan Bisnis, 2023)
This study is aimed to analyze the effect of working capital management ratio such as average days of receivable, average days of inventory, average days of payable toward retail firms’ performance listed on IDX period 2018-2022 proxied with return on asset. Retail firms which have the characteristic of keeping high level of inventory, is related with the efficiency of working capital management in achieving the high profit. The sample selection was done by purposive sampling method and obtained 6 retail companies. The study used the quantitative approach such as descriptive statistical test, classical assumption test, panel data regression analysis using Eviews 12. The result obtained average days of receivable has positive and insignificant effect on firms’ performance, average days of inventory has positive and significant effect on firms’ performance, average days of payable has negative and significant effect on firms’ performance.